2000
DOI: 10.1016/s0928-8244(00)00223-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the secreted macromolecular immunogens of Staphylococcus aureus by analysis of serum

Abstract: The ability of sera to recognise secreted macromolecules of Staphylococcus aureus was examined by ELISA and Western immunoblotting. Individual secreted proteins were also studied using both human sera and sera from rabbits immunised with secreted macromolecules. Patients sera showed a wide range of IgG antibody titres to secreted macromolecules and whole bacteria. Controls showed a significantly lower IgG response. Western immunoblotting revealed that a significant number of secreted proteins were recognised b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Some investigators used whole cells or extracts [16,20], however, others pointed out the complexity caused by IgG-binding protein A and the potential advantages of using recombinant antigens [16,17,20]. Some investigators reported that patients with infection generally had higher antibody levels against purified proteins or recombinant antigens than healthy controls, and observed degrees of overlap between patients with infection and control subjects [8,13,33,44] similar to those reported here. None pursued the IgG responses for use in diagnostic applications.…”
Section: Sensitivity (%)supporting
confidence: 65%
See 1 more Smart Citation
“…Some investigators used whole cells or extracts [16,20], however, others pointed out the complexity caused by IgG-binding protein A and the potential advantages of using recombinant antigens [16,17,20]. Some investigators reported that patients with infection generally had higher antibody levels against purified proteins or recombinant antigens than healthy controls, and observed degrees of overlap between patients with infection and control subjects [8,13,33,44] similar to those reported here. None pursued the IgG responses for use in diagnostic applications.…”
Section: Sensitivity (%)supporting
confidence: 65%
“…Additionally, while serum diagnostics are available for several microbial pathogens, no host immunity test is available for S aureus infections. To this end, several groups have described the anti-S aureus humoral immune response in physiologic and pathological situations [12,13,33,39,41,42,44]. Gedbjerg et al [15] described an antiglucosaminidase antibody test to assess infection and prognosis in patients undergoing orthopaedic surgery who have a confirmed S aureus infection.…”
Section: Introductionmentioning
confidence: 99%
“…Our ELISA analyses with selected staphylococcal proteins suggested that the antistaphylococcal antibody repertoires from healthy and diseased individuals overlap. Similarly, a proteomic analysis showed that sera from healthy donors and infected patients recognize a similar pattern of antigens from S. aureus (47). These data prompted us to identify staphylococcal antigens by the use of antibodies from high-titer sera from healthy people in a comprehensive genomic screening method (14).…”
Section: Figmentioning
confidence: 99%
“…The anti-S. aureus antibody patterns from healthy individuals and patients overlap strongly (Dryla et al, 2005;Royan et al, 2000;Vytvytska et al, 2002). There are two non-exclusive explanations for this: (1) The antibodies observed in healthy individuals are generated in response to minor infection, and (2) the protein expression patterns of S. aureus in colonization and invasion are similar.…”
Section: Infectionmentioning
confidence: 99%